1972
DOI: 10.1002/art.1780150409
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic studies of serum uric acid levels among micronesians

Abstract: Data from epidemiologic studies of Chamorro and Palauan populations of Micronesia were analyzed for associations of serum uric acid levels with other characteristics of the populations. The mean serum uric acid levels for those groups were significantly higher than those reported for Western populations, but the frequency distribution patterns were similar, being unimodal and slightly skewed toward higher values. Analysis by geographic subgroups showed differences in mean serum uric acid levels, but those diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Age distribution (Table 1) reflects the early onset of gout, noted clinically in Chamorros (Reed et al, 1970(Reed et al, , 1972. While it cannot be proven that Chamorros 500 years ago had the same degree of hyperuricemia and gout as today's Chamorros, observation of similar frequencies of osseous lesions, different in character from those found in other rheumatologic diseases (Leisen et al, 1987;Rothschild andWoods, 1988, 1991a;Rothschild et al, l988,1990Rothschild et al, l988, ,1992a, would support the continued presence of a disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age distribution (Table 1) reflects the early onset of gout, noted clinically in Chamorros (Reed et al, 1970(Reed et al, , 1972. While it cannot be proven that Chamorros 500 years ago had the same degree of hyperuricemia and gout as today's Chamorros, observation of similar frequencies of osseous lesions, different in character from those found in other rheumatologic diseases (Leisen et al, 1987;Rothschild andWoods, 1988, 1991a;Rothschild et al, l988,1990Rothschild et al, l988, ,1992a, would support the continued presence of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, 10% of Chamorro men and 16% of Chamorro women complained of joint pain, 4% of males and 3% of females had a "doctor's diagnosis of gout," and 2% of men and 7% of women had kidney stones (Burch et al, 1966;Healey et al, 1966;Reed et al, 1972). As there is likely a substantial degree of genetic continuity between the high prevalence of gout in Chamorros of today and the ancient Chamorros employed in this study (Underwood, 1976), the present skeletal sample is a reasonable one to employ in assessing the population characteristics of gout.…”
mentioning
confidence: 99%
“…Correlation between hyperuricemia, metabolic arthritis and type 2 diabetes was observed by Berowitz and Mikkelson [17,18]. In the other publications this correlation wasn't confirmed [19,20]. Yano, Klein, Hermann and associates informed about negative correlation between level of uric acid in serum and diabetes [21][22][23].…”
Section: Discussionmentioning
confidence: 97%
“…Several reports 36 "" 3844 ' 45 have attested to the high prevalence of hyperuricemia and gout in the Pacific area. The association of hyperuricemia and diabetes commented on by Prior et al 37 was not found in the Chamorros or Carolinians of Micronesia by Reed.…”
Section: Discussionmentioning
confidence: 99%